STUDI TENTANG STRATEGI DAKWAAN TGH. MUHTAR AMIN DALAM MENGATASI PERILAKU MASYARAKAT DI KECAMATAN TERENGAN, DESA PEWIANG TIMUR - Suhaili (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
This study aims to determine the da'wah strategy of TGH. Muhtar Amin in responding to the behavior of the community in the hamlet of Terengan, East Pemenang Village . The results of the study show that a strategy does not have to be written but can come directly from the mind and then realized. TGH. Muhtar Amin did not make a da'wah strategy in writing or through meetings, but in practice there are several actions that he did. He paid attention to four very important elements in making a strategy, namely strengths, da'wah opportunities, weaknesses and threats. So that several actions emerged that he took, including: a) Proportionalization of Da'wah Material; b) Material Directly From the Book; c) Effectiveness and Time Efficiency; d) Bringing Other Tuan Gurus to his Ta'lim Assembly; e) Separating Da'wah Among the Community. To strengthen his da'wah strategy, of course there are supporting factors in carrying out da'wah. There are at least two supporting factors for TGH. Muhtar Amin in carrying out his da'wah, namely: a) Strategic da'wah location; b) Founder of the First Majlis in Terengan Hamlet, Pemenang Timur Village; c) Has a congregation from various levels of society; d) TGH. Muhtar Amin is one of the oldest religious figures so that by implementing several strategies, as well as the existence of several supporting factors as well as obstacles and efforts related to his da'wah in Pemenang Timur Village, where the nature of the community is heterogeneous or diverse, it can be carried out well and evenly.